PENGARUH KEINOVASIAN DAN KARAKTERISTIK GURU TERHADAP KINERJA GURU DI SMP NEGERI SE-KABUPATEN BENGKAYANG - Erawati, Eka; Aswandi, Aswandi; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This research focuses on teacher performance that is related with teacher innovation and their characteristics, in terms of gender, educational background, and work experience. Teacher innovation is focused on: (a) associating skills, (b) questioning, (c) observing, (d) experimenting, and (e) networking. The purpose was to determine how the influence of teacher innovation and its characteristics on the performance of Junior High School (SMPN) teachers in Bengkayang. This research uses quantitative research methods with the use of a questionnaire as a data collection tool. The subjects were 144 teachers with characteristics as permanent school teachers, two years experience, and a bachelor?s degree (S1). They were taken based on the distribution of sub-arrays and took 6 teachers in each school. Based on data analysis, the results are: (1) Teacher innovation influences the performance of SMPN teachers in Bengkayang; (2) Teacher characteristics in terms of gender, educational background, and work experience have an influence on the performance of SMPN teachers in Bengkayang; and (3) Teacher innovation and teacher characteristics in terms of gender, educational background, and work experience have a simultaneous influence on the performance of SMPN teachers in Bengkayang. The conclusion of this study is the level of teacher innovation and its characteristics in terms of gender, educational background, and work experience simultaneously have a significant effect on the performance of of SMPN teachers in Bengkayang by 62.50%, while the other 37.50% is influenced by other variables. Suggestions in this study are: (1) For teachers, they should maintain and improve its performance which is generally good; (2) Teachers should continue to improve their innovative power through a lot of reading, attending training activities or seminars, and enriching themselves through supporting information on self-innovation; (3) For the Department of Education, should improve programs that can increase teacher motivation. Some suggested programs such as in the fields of technology, scientific work, the development of new teaching methods based on local wealth, and so on; and (4) It is recommended for other researchers to examine from different perspectives and methods, so that they can see more clearly, in depth, and detail for other variables. Keywords: Characteristic, Innovation, Teachers? Performance